PENGEMBANGAN KAPASITAS (CAPACITY BUILDING) UNTUK MENINGKATKAN PELAKSANAAN DANA DESA : (Studi kasus pada Kampung Kondo Distrik Naukenjerai Kabupaten Merauke) - yuliana evarista (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2022)
Capacity building is the most important part in various aspects of life, one of which is in government agencies to improve capabilities and make the performance of the apparatus better in carrying out their duties. The purpose of this study was to determine the capacity building of the village head and village apparatus (study in Kondo Village, Naukenjerai District, Merauke Regency). Data collection techniques using interview techniques (based on interview guidelines), observation and documentation. Furthermore, the data analysis carried out consisted of three stages, namely data condensation, data presentation and drawing conclusions. The results of this study indicate that capacity building has not gone well. This can be seen in several aspects such as the capacity of village apparatus resources which are not good enough, seen from the level of education and understanding of the knowledge of the apparatus which is still low. There are factors that support and hinder capacity building in the implementation of village funds. The supporting factors are Joint Commitment, Leadership and Budget, while the inhibiting factors are weak human resources, and limited facilities and infrastructure.